2007
DOI: 10.1242/jeb.002030
|View full text |Cite
|
Sign up to set email alerts
|

Variation in salinity tolerance, gill Na+/K+-ATPase,Na+/K+/2Cl– cotransporter and mitochondria-rich cell distribution in three salmonids Salvelinus namaycush, Salvelinus fontinalis and Salmo salar

Abstract: SUMMARY We compared seawater tolerance, gill Na+/K+-ATPase and Na+/K+/2Cl– cotransporter (NKCC)abundance, and mitochondria-rich cell (MRC) morphology of three salmonids,lake trout Salvelinus namaycush, brook trout Salvelinus fontinalis and Atlantic salmon Salmo salar. They were transferred directly from 0 p.p.t. (parts per thousand; freshwater) to 30 p.p.t. seawater, or transferred gradually from 0 to 10, 20 and 30 p.p.t. at 1-week intervals and kept in 30 p.p.t. for 3 weeks. The survival rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 41 publications
10
57
0
Order By: Relevance
“…Lines in boldface are instances where the mean intergenic distance (IGD) of genes differentially expressed in Arctic charr is significantly less than the mean IGD of the corresponding stickleback chromosome. man), which is consistent with previous findings and expectations (7,22,30,37,46,47,51,52,55,57,65). It is also possible that changes in the transcription rates of these genes were missed due to the experimental design, as sampling occurred at a single time-point, rather than at multiple-time points spanning pre-and postseawater exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Lines in boldface are instances where the mean intergenic distance (IGD) of genes differentially expressed in Arctic charr is significantly less than the mean IGD of the corresponding stickleback chromosome. man), which is consistent with previous findings and expectations (7,22,30,37,46,47,51,52,55,57,65). It is also possible that changes in the transcription rates of these genes were missed due to the experimental design, as sampling occurred at a single time-point, rather than at multiple-time points spanning pre-and postseawater exposure.…”
Section: Discussionsupporting
confidence: 90%
“…With the anti-NKCC1 antibody, we found two bands of $200 and $130 kDa in the longhorn sculpin gill. Because we found only single (CFTR, NKA) or double bands (NKCC1) with our western blots, and these findings mirror those from other teleosts (Tipsmark et al, 2002;Hiroi and McCormick, 2007), we quantified protein differences with dot blots (total protein, not proteins separated by molecular weight).…”
Section: Westerns and Dot Blotssupporting
confidence: 56%
“…Studies in euryhaline fishes, such as the killifish (Fundulus heteroclitus), or anadromous fishes such as the rainbow trout (Oncorhynchus mykiss), brown trout (Salmo trutta), or Atlantic salmon (S. salar) have explored the effects of changes in environmental salinity on gill ion transporter density (e.g. Mancera and McCormick, 2000;Seidelin et al, 2000;Pelis et al, 2001;Marshall et al, 2002;Singer et al, 2002;Scott et al, 2004;Hiroi and McCormick, 2007). In general, when these fishes move from FW/brackish water to marine waters, there is a rapid increase in plasma [Na…”
mentioning
confidence: 99%
“…Diluted seawater was used for the experiment because a previous study showed that Biwa salmon was intolerant to full-strength seawater (11). When juvenile salmon are transferred from freshwater to seawater, a typical response is transitional increases in blood sodium and chloride ion concentrations within 24 h followed by a reduction to the levels comparable to those in freshwater (7,15). In the present study, the sham-treated Biwa salmon showed increases in both sodium and chloride ion concentrations within 24 h, and it stayed high for additional 2 days.…”
Section: Discussionmentioning
confidence: 99%